(untitled) (Plant Bulletin, 2025)
Mango (Mangifera indica L.) is a vital fruit crop is known as the King of fruits owing to its unique aroma, taste, and high nutritional value. Characterizing mango varieties is crucial for their improvement and breeding programs. This study was carried out at the Horticultural Research Station Bahawalpur, to evaluate and characterise Mangifera indica varieties utilising three mango varieties Sindhri, Langra, and Kingstone pride using a morpho-biochemical approach. Different Morphological Parameters (fruit length, width, stone, peel, pulp and fruit weight) and Biochemical Parameters (TSS, TA, Ascorbic acid, total phenolic content, anthocyanin, carotenoids content, POD and CAT activity) were assessed. Results concludes that in among these varieties Langra has better morphological traits than Sindhri and Kingstone pride while in terms of fruit quality Sindhri was best. Moreover, Kingstone pride depicted better antioxidative properties. The findings of this study support the hypothesis that significant variation exists among genotypes based on their Morphological and biochemical characteristics. Detailed characterization is therefore an essential step for starting a breeding program.